MOTIVASI PEGAWAI PADA KIOS PONSEL BERADA DI KELURAHAN KEDUNG SARI KECAMATAN SUKAJADI KOTA PEKANBARU - Oktaviana, Neysi; Jas, Jasfar; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack : The purpose of this study was to determine employee motivation at the mobile phone kiosk in Kedung Sari Village, Sukajadi District, Pekanbaru City. This study uses a descriptive method with a quantitative approach. The sample in this study was 20 for questionnaire surveys and 35 people for survey questionnaires with a sampling method for random samples, that is samples without taking into account the layers in the population. The technique to collect data using a questionnaire. Techniques for data analysis using the percentage formula. The results of this study indicate that the motivation of employees in the family is classified as good, the motivation of employees in their profession is classified as good, the motivation of employees in performance is very good, the motivation of employees in good opportunities and the motivation of employees in compensation in the form of money is good. The five motivation indicators are then combined in combination as good interpretations.Key Words: Motivation, Employees